Desarrollo de una secuencia didáctica a partir del cambio conceptual de los aspectos Morfo-Ecológicos de las Mariposas, en estudiantes de grado cuarto de la Institución Educativa Inem José Celestino Mutis de Armenia-Quindío (2019)
A research has been made with the purpose of identify the previous ideas that students have of the morpho-ecological aspects of butterflies to develop and implement a didactic sequence based on conceptual change.